The effect of effectuation and causation approach on entrepreneurial orientation in the presence of leader dominance and self-efficacy - Jun, Ma; Ariyesti, Fitri Rini; Ali, Sumran; Xiaobao, Peng (Journal of entrepreneurship in emerging economies, 2023)
Purpose Entrepreneurial orientation (EO) has witnessed a daunting rise in firm-level practices; to some extent, it has been augmented by the factors such as globalization and technological shift. The wide variety of literature has explained the importance of EO for firm performance. However, it has not yet been explored at a firm-level the approaches of causation and effectuation through the prism of leader traits such as leader dominance and self-efficacy as administrative ability and EO as strategic manoeuvring with strategic decisions obliged as a spin of firms. Design/methodology/approach The authors used the quantitative method to analyse the proposed relationships. For this reason, the authors targeted the Chinese firms to collect the data through the semi-structured survey from December 2020 to March 2021 and contributed to the literature by investigating 480 valid responses of leaders from Chinese firms. Findings The findings support the incorporated view of causation and effectuation on EO, which serve as vital strategic manoeuvring along with leader traits for firm stability and growth. Practical implications This study assists the decision-makers (including the top management team, Chief Financial Officer and Chief Executive Officer choose the particular approach (effectual or causal) to create the new venture/new product/new process or scale up the existing firm on another level for optimal benefits by considering their existing resources. Originality/value EO is a unidirectional process with three dimensions: innovativeness, proactiveness and risk-taking that could directly favour the firm by considering the well-known approaches (effectuation and causation) in crisis circumstances (like Covid-19). These approaches help the executives enhance their firm’s performance and maintain its sustainability and stability in crisis conditions by effectively using the available resources within its boundaries.